Strategi Pelatihan Luring dalam Menyiapkan Kepemimpinan Calon Kepala Sekolah Dasar Profesional: Pengabdian - Zuhad Ahmad; Hamzah Puadi Ilyas (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service initiative aims to enhance the competencies of prospective elementary school principals through offline-based training. The program targeted 20 prospective principals from Simalungun Regency, North Sumatra, who had no prior leadership experience in schools. Conducted over the span of one week, the training utilized lectures, discussions, group work, and case studies. The core training materials covered character education, school managerial skills, coaching for teachers and staff supervision, and entrepreneurial development. Evaluation methods included pre-tests, post-tests, and participant satisfaction questionnaires. The results demonstrated a significant improvement in participants' understanding and readiness to assume the role of school principals. Participants’ average scores increased by 35%, and satisfaction levels reached 92%. This training bridged the gap between participants’ initial preparedness and the professional demands of school leadership. The offline and context-based learning approach proved effective in fostering applicable leadership skills. Moreover, the program reinforced collaboration between universities and local governments in preparing reflective and professional educational leaders for elementary schools.